Inappropriate complementary feeding practice increases risk of stunting in children aged 12-24 months - Hijra, Hijra; Fatimah-Muis, Siti; Kartasurya, Martha Irene (Universa Medicina, 2016)
BackgroundIn 2013, the prevalence of stunting in Central Sulawesi province was 41%, which was higher than the national prevalence of 37.2%. Complementary feeding practice, infectious disease, history of exclusive breastfeeding, birth weight and birth length were assumed to contribute to the prevalence of stunting. The objective of the present study was to identify the risk factors for stunting among children aged 12 to 24 months.MethodsThis study was conducted using a case control design. Subjects were children aged 12-24 months, consisting of 58 cases and 58 controls. Data were obtained with a body length infantometer. Data on complementary feeding practices, history of exclusive breastfeeding, and history of infectious diseases were obtained using questionnaires. Nutrient intakes were measured by semi quantitative food frequency questionnaires. Data on birth weight and birth length were obtained from the buku KIA (maternal and child health record). Data were analyzed by chi-square and logistic regression tests. ResultsThere was no difference in sex, BMI, and parental education between cases and controls (p>0.05). After controlling for history of exclusive breastfeeding and birth weight, the risk factors for stunting were inappropriate complementary feeding practice in terms of quantity and quality (OR=8.26; 95% CI: 2.69-25.44), history of diarrhea (OR=4.73; 95% CI: 1.08-20.69), birth length (OR=5.11; 95% CI: 1.69-15.46) and respiratory tract infection (OR=5.30; 95% CI: 1.03-27.23). Inappropriate complementary feeding practice was the most dominant factor for stunting.ConclusionInappropriate complementary feeding practice increased the risk of stunting in 12-24 months old children by 8.26. This study confirms the need to scale up interventions during the first 2 years of life, including appropriate infant feeding practices.